2012
DOI: 10.1371/journal.pone.0039935
|View full text |Cite
|
Sign up to set email alerts
|

CRF Induces Intestinal Epithelial Barrier Injury via the Release of Mast Cell Proteases and TNF-α

Abstract: Background and Aims Psychological stress is a predisposing factor in the onset and exacerbation of important gastrointestinal diseases including irritable bowel syndrome (IBS) and the inflammatory bowel diseases (IBD). The pathophysiology of stress-induced intestinal disturbances is known to be mediated by corticotropin releasing factor (CRF) but the precise signaling pathways remain poorly understood. Utilizing a porcine ex vivo intestinal model, the aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 51 publications
2
145
3
3
Order By: Relevance
“…62,84 Plenty of work has been done to verify the concept that MCs contribute to stress induced gut dysfunction. For example, MCs mediate stress induced intestinal barrier disruption [85][86][87] and visceral hypersensitivity 82,88,89 due to the release of tryptase, TNF-α, 86 and histamine. 82 Peripheral administration of H 1 R antagonists fexofenadine and ebastine are capable of reversing post stress visceral hypersensitivity in rats.…”
Section: Central Stress: Psychological Distress and Negative Life Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…62,84 Plenty of work has been done to verify the concept that MCs contribute to stress induced gut dysfunction. For example, MCs mediate stress induced intestinal barrier disruption [85][86][87] and visceral hypersensitivity 82,88,89 due to the release of tryptase, TNF-α, 86 and histamine. 82 Peripheral administration of H 1 R antagonists fexofenadine and ebastine are capable of reversing post stress visceral hypersensitivity in rats.…”
Section: Central Stress: Psychological Distress and Negative Life Eventsmentioning
confidence: 99%
“…91 Recently, evidence supported that stress induced CRF, acting on the CRF1 and CRF2 receptors, should be the key factors in MCs degranulation. 62,85,86 Stress triggers the increase in intestinal paracellular permeability via mast cell dependent release of proteases, which could be reproduced by peripheral administration of CRF, and blocked by CRF 1/2 receptor antagonist, mast cell stabilizers, and protease inhibitors. 86 …”
Section: Central Stress: Psychological Distress and Negative Life Eventsmentioning
confidence: 99%
“…Tumor necrosis factor- (TNF-) has been shown to increase intestinal permeability through nuclear factor-kappa B activation in association with nuclear factor-kappa B-dependent downregulation of zona occludens protein-1 expression and alteration in junctional localization in Caco-2 cells, 85 and through myosin light chain kinase phosphorylation. 86 More recently, using a porcine ex vivo intestinal model, Overman et al 87 found that CRF increased intestinal paracellular permeability via mast cell dependent release of TNF- and proteases. On the other hand, the tryptase released by mast cells upon activation has been shown to induce TJs disassembly through the activation of proteinase-activated receptor-2 of the epithelial cells.…”
Section: Permeabilitymentioning
confidence: 99%
“…2), psychophysiological stress (such as adverse life events, catching cold, and intestinal infection) activates the hypothalamic-pituitary-adrenal (HPA) axis (Mayer, 2000;Chang et al, 2009;Kennedy et al, 2014). The central and intestinal corticotropin releasing factor (CRF) increases and activates intestinal MCs (Barreau et al, 2007;Overman et al, 2012). Activated MCs degranulate and release mediators such as NGF and tryptase.…”
Section: Ngf-mc-nerve Interaction In Ibs-d Pathophysiologymentioning
confidence: 99%